Galerie Krikhaar te gast in Museum van Bommel-Van Dam Venlo. - Krikhaar, Herman (Venlo : Museum Van Bommel Van Dam, 1974)
Chagall, Marc ; Appel, Karel ; Corneille ; Rooskens, Anton ; Constant ; Saura, Antoni ; Maryan ; Tajiri ; Baj, Enrico ; Schäperkötter ; Avenali ; Erro ; Müller, Robert ; de Lussanet, Paul ; Sadkowsky ; Wylie, James ; Huig, Henk ; Cottavoz ; Jonk, Nic ; Arman ; Van Hoeydonck, Paul ; etc.
Galerie Krikhaar te gast in Museum van Bommel-Van Dam Venlo, 4.5 - 10.6.1974
Nederlands
kunstcatalogus
Keywords: Krikhaar, Herman